2013
DOI: 10.1371/journal.pone.0070698
|View full text |Cite
|
Sign up to set email alerts
|

Direct Detection of Alternative Open Reading Frames Translation Products in Human Significantly Expands the Proteome

Abstract: A fully mature mRNA is usually associated to a reference open reading frame encoding a single protein. Yet, mature mRNAs contain unconventional alternative open reading frames (AltORFs) located in untranslated regions (UTRs) or overlapping the reference ORFs (RefORFs) in non-canonical +2 and +3 reading frames. Although recent ribosome profiling and footprinting approaches have suggested the significant use of unconventional translation initiation sites in mammals, direct evidence of large-scale alternative pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
250
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 197 publications
(255 citation statements)
references
References 58 publications
4
250
0
1
Order By: Relevance
“…The abundance-alternative ORFs were corroborated [161], supporting the idea that alternative ORFs provide unexpected complexity for immunosurveillance to exploit. Some peptides identified derive from initiation at a near-cognate non-AUG codon [159,160].…”
Section: Junk? Really?mentioning
confidence: 54%
“…The abundance-alternative ORFs were corroborated [161], supporting the idea that alternative ORFs provide unexpected complexity for immunosurveillance to exploit. Some peptides identified derive from initiation at a near-cognate non-AUG codon [159,160].…”
Section: Junk? Really?mentioning
confidence: 54%
“…Another study, identified 1,259 novel peptides [46], by matching the spectra of different HPLC-MS data-sets (16 in total, covering a range of different human samples) to a custom database of predicted ORFs within annotated transcripts (mapping to UTRs and overlapping CDS'), suggesting that the translation of these "alternative" smORFs could be a wide-spread phenomenon. Interestingly, the majority of these peptides were identified in plasma and serum samples (1,118 / 1,259), implying that they could be secreted, although the reason or mechanism leading to this remains unknown (Table S1).…”
Section: Detection Of Smorf Peptides By Mass Spectrometrymentioning
confidence: 99%
“…Phylogenetic evidence also strongly supports the functional importance of this uORF product in addition to the uORF's regulatory role in providing stress resistance to the translation of the annotated CDS 45. The detection of a product translated from an ORF in the 3′UTR of the human CHTF8 gene has also been reported 43, 44. Indeed in GWIPS‐viz, a high ribosome occupancy can be seen in the 3′UTR region of the human CHTF8 transcripts (Fig.…”
mentioning
confidence: 67%